Bright star, shadow plays: Susan Roces' construction of the postwar "Babaeng Pilipina", and the "Chinese Mestizo's" dDisappearance into the "Filipino" - Chua, Gershom C.
This study explores the complex interplay of ethnic identity, stardom, and star image construction in the life and career of Chinese Mestizo movie queen Susan Roces, particularly as it relates to her agency and liminal identity as a Chinese-European mestizo. It examines how Roces constructed the postwar Babaeng Pilipina ideal onscreen and employed strategies to naturalize and obfuscate the mestizo and colonial origins of its constitutive parts, which speak to the broader socio-historical dynamics of Chinese Filipinos and their navigation of mestizo liminality in a postcolonial society. The concept of "ethnic choices" emerges as central to understanding Roces' agency as a mestiza individual renegotiating her ethnic identification amidst the very public nature of film stardom. Drawing from a branch of film studies known as star studies, the study treats Roces as both star text and an agent of the film industry, an an analysis of her star image and career navigation is treated as a micro-historical narrative of the very public ethnic negotiation and renegotiation of the Chinese Mestizo's liminal ethnic identification, contextualized by macro-historical developments in the Chinese Filipino experience.